Identification of a chemical probe for family VIII bromodomains through optimization of a fragment hit - Gerstenberger, BS; Trzupek, JD; Tallant, C; Fedorov, O; Filippakopoulos, P; Brennan, PE; Fedele, V; Martin, S; Picaud, S; Rogers, C; Parikh, M; Taylor, A; et al. (American Chemical Society, 2016)
The acetyl post-translational modification of chromatin at selected histone lysine residues is interpreted by an acetyl-lysine specific interaction with bromodomain reader modules. Here we report the discovery of the potent, acetyl-lysine-competitive, and cell active inhibitor PFI-3 that binds to certain family VIII bromodomains while displaying significant, broader bromodomain family selectivity. The high specificity of PFI-3 for family VIII was achieved through a novel bromodomain binding mode of a phenolic headgroup that led to the unusual displacement of water molecules that are generally retained by most other bromodomain inhibitors reported to date. The medicinal chemistry program that led to PFI-3 from an initial fragment screening hit is described in detail, and additional analogues with differing family VIII bromodomain selectivity profiles are also reported. We also describe the full pharmacological characterization of PFI-3 as a chemical probe, along with phenotypic data on adipocyte and myoblast cell differentiation assays.